2016
DOI: 10.1039/c6nr00605a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for excitation-dependent photoluminescence from graphene quantum dots and other graphene oxide derivates: consensus, debates and challenges

Abstract: Luminescent nanomaterials, with wide applications in biosensing, bioimaging, illumination and display techniques, have been consistently garnering enormous research attention. In particular, those with wavelength-controllable emissions could be highly beneficial. Carbon nanostructures, including graphene quantum dots (GQDs) and other graphene oxide derivates (GODs), with excitation-dependent photoluminescence (PL), which means their fluorescence color could be tuned simply by changing the excitation wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
268
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(300 citation statements)
references
References 144 publications
17
268
1
2
Order By: Relevance
“…In addition, similarly to the excitation-dependent fluorescence properties of carbon quantum dots, polymer dots, and other fluorescent NPs, those of bAPSC NPs were observed to be consistent with their emission spectra [33,34,35]. Although the exact mechanism remains unclear, different organic fluorescent NPs have shown similar behavior [30,32,33,36,37]. Sun et al reported that polymer dots based on a PEI–polylactic acid (PLA) copolymer showed excitation-dependent fluorescence behavior with a significant redshift [30].…”
Section: Resultsmentioning
confidence: 86%
“…In addition, similarly to the excitation-dependent fluorescence properties of carbon quantum dots, polymer dots, and other fluorescent NPs, those of bAPSC NPs were observed to be consistent with their emission spectra [33,34,35]. Although the exact mechanism remains unclear, different organic fluorescent NPs have shown similar behavior [30,32,33,36,37]. Sun et al reported that polymer dots based on a PEI–polylactic acid (PLA) copolymer showed excitation-dependent fluorescence behavior with a significant redshift [30].…”
Section: Resultsmentioning
confidence: 86%
“…As it can be seen, a wavelength-dependent behavior was found. According to the literature, this can be related to the NPs size [51] and/or energy traps created by surface groups [52]. Thus, the demonstration of quantum phenomenon is not an easy task to be performed in a simple lab experiment.…”
Section: Discussionmentioning
confidence: 99%
“…17 Teng and co-workers have also found such excitation wavelength independent photoluminescence of GO. 50 According to Gan et al, 51 giant red edge effect may be one of the origin of excitation wavelength dependent photoluminescence of GO quantum dots. But, such observation is absent in the GO, synthesized by us, because of different characteristics with respect to GO quantum dots.…”
Section: B Absorption Spectramentioning
confidence: 99%